Efektivitas Kebijakan Penal dan Non-Penal dalam Pemberantasan Tindak Pidana Terorisme di Indonesia terhadap Implementasi Undang-Undang Nomor 5 Tahun 2018 - Aswindari Harahap; Sumarno Sumarno; Meina Alvionita br Purba; Donly Calner Aruan (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2026)
This study aims to analyze the effectiveness of penal and non-penal policies in combating terrorism in Indonesia and to identify juridical and criminological challenges in their implementation. The study is grounded in the evolving dynamics of terrorism, particularly reflected in the case of Jamaah Ansharut Daulah (JAD), which demonstrates that weakening organizational structures does not necessarily eliminate radical ideology. This research employs a normative legal method using statutory, conceptual, and case approaches. The findings reveal that penal policies under Law Number 5 of 2018 are effective in law enforcement and prevention of terrorist attacks but have not addressed the ideological roots of radicalization. Meanwhile, non-penal approaches, particularly deradicalization programs, face limitations in preventing recidivism and ensuring sustainable social reintegration. The main challenges include ambiguous legal norms, potential human rights violations, and complex criminological factors such as ideology, social networks, and digital transformation. This study highlights the necessity of integrating penal and non-penal strategies based on human rights principles, emphasizing preventive and rehabilitative approaches to achieve a more effective and sustainable counter-terrorism framework.